Spousal violence among reproductive age group women - A community-based cross-sectional study - Ashwini Katole; Ajeet Saoji; Mohan Kumar (Wolters Kluwer Medknow Publications, 2023)
Background: Spousal or intimate partner violence is the most common form of domestic violence and is a preventable cause of morbidity and mortality in women. The aim of this study was to estimate the prevalence of spousal violence, various types of spousal violence, and the factors associated with it among reproductive age group women. Materials and Methods: This was an analytical cross-sectional study conducted in the Urban Health Training Center area of a tertiary care teaching hospital in Nagpur, India, among married women between 15 and 49 years of age who were selected using systematic random sampling. The data was collected from a sample of 373 women by face-to-face interview and analyzed using Statistical Package for the Social Sciences (SPSS) v21. Results: The prevalence of spousal violence among reproductive age group (15-49 years) women was found to be 59.7%, with emotional violence (54.1%) being the most common, followed by physical (51.2%) and sexual (43.4%) violence in that order. Regular alcohol consumption of husband had the highest odds of spousal violence among women (odds ratio [OR] 12.51, 95% confidence interval [CI] 6.51-24.03). Other factors associated with spousal violence among reproductive age group women were early age at marriage, literacy and employment of women and husband, lack of emotional support from the family members, and dowry-related problems in the family. Conclusion: A multifaceted approach including legal measures, empowerment of women, and sociocultural factors involving families, institutions, governmental, nongovernmental, and civil society organizations is the need of the hour.